Quantification of skin lesions with a 3D stereovision camera system: validation and clinical applications. Issue 1 (20th June 2012) - Skvara, Hans; Burnett, Patrick; Jones, Julie; Duschek, Nikolaus; Plassmann, Peter; Thirion, Jean‐Philippe
<x xml:space="preserve">Abstract</x> Background/purpose Three‐dimensional (3D) imaging of the skin is a challenging technique. A new 3D digital camera system has been developed that enables 3D reconstruction of the skin and subsequently allows volumetric quantification. Herein we present validation data on calibrated phantoms and the clinical application of this technology. Methods Absolute and relative geometric 3D measurements were validated with a static imaging phantom manufactured by a metrology institution and a dynamic imaging phantom adjustable for different volume quantities, respectively. Consecutively, in a clinical study, 3D baseline and follow up images from 27 basal cell carcinomas under topical therapy were captured for volumetric analysis. Results Validation experiments have demonstrated an average accuracy for surface position of 55 μm and a precision of 8 μm, as well as excellent correlation (0.999) between injected and measured volumes. The geometric baseline analysis of 27 basal cell carcinomas exhibited a high correlation and agreement between 2D and 3D surface measurements. Under topical therapy, it was possible to gain statistically significant differences between verum‐ and vehicle‐treated basal cell carcinomas when analyzing geometric measurements of 3D volume (P = 0.01) and 3D surface (P = 0.001). Conclusion In our study we were able to demonstrate that this newly developed 3D camera system offers a precise objective dimensional representation of the skin. This technique is easily applicable and sensitive enough to measure small differences in area and volume before and after intervention.